2021
DOI: 10.1007/s00253-021-11112-5
|View full text |Cite
|
Sign up to set email alerts
|

A bottom-up approach towards a bacterial consortium for the biotechnological conversion of chitin to l-lysine

Abstract: Chitin is an abundant waste product from shrimp and mushroom industries and as such, an appropriate secondary feedstock for biotechnological processes. However, chitin is a crystalline substrate embedded in complex biological matrices, and, therefore, difficult to utilize, requiring an equally complex chitinolytic machinery. Following a bottom-up approach, we here describe the step-wise development of a mutualistic, non-competitive consortium in which a lysine-auxotrophic Escherichia coli substrate converter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…A synthetic consortium composed of a chitin degrading E. coli strain and a C. glutamicum strain producing nitrogenous compounds has been used to develop chitin-based production ( Vortmann et al, 2021 ). In this proof-of-concept study, the chitin monomer N -acetylglucosamine is hydrolyzed by a lysine-auxotrophic E. coli strain to yield acetate and glucosamine.…”
Section: Engineering Corynebacterium Glutamicum Fo...mentioning
confidence: 99%
See 2 more Smart Citations
“…A synthetic consortium composed of a chitin degrading E. coli strain and a C. glutamicum strain producing nitrogenous compounds has been used to develop chitin-based production ( Vortmann et al, 2021 ). In this proof-of-concept study, the chitin monomer N -acetylglucosamine is hydrolyzed by a lysine-auxotrophic E. coli strain to yield acetate and glucosamine.…”
Section: Engineering Corynebacterium Glutamicum Fo...mentioning
confidence: 99%
“…Acetate is the only carbon source for the engineered E. coli strain, whereas the lysine-secreting C. glutamicum producer strain was engineered to only use glucosamine. Chitin degrading enzymes (chitinase, chitin deacetylase and glucosaminidase) had to be added to the growth media, but they may be synthesized and secreted by the E. coli strain used ( Vortmann et al, 2021 ).…”
Section: Engineering Corynebacterium Glutamicum Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial co-cultures, mostly referred as microbial/bacterial consortia, have been investigated to much greater detail and possess wider applications. In fact, bacterial consortia are fabricated for specific biotechnological goals (Vortmann et al, 2021 ). Synthetic microbial consortia borrow ecological concepts, such as amensalism and commensalism, to engineer high performance multi-species systems (Sgobba and Wendisch, 2020 ).…”
Section: The Metabolic Black-box Of Fungal Co-culturesmentioning
confidence: 99%
“…Recently, it could also be demonstrated that production of sarcosine from the pentose xylose was more efficient than that from glucose ( Mindt et al, 2019b ). Additionally, less processed substrates such as lignocellulosic residuals, rich straw, wheat bran and plant mass hydrolysates, chitin, the biorefinery sidestream pyrolysis water, and wheat sidestream concentrate (WSC) from the starch and paper industries could be harnessed by C. glutamicum as carbon sources ( Gopinath et al, 2011 ; Lange et al, 2017 ; Mindt et al, 2019a ; Sasaki et al, 2019 ; Prell et al, 2021a ; Vortmann et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%